Mechanisms to manage intellectual property in collaborative innovation projects (2016)
ABSTRACT: This paper presents some mechanisms for managing Intellectual Property (IP) in collaborative innovation projects, especially those using co-creation techniques. The mechanisms selection was made from a documentary review that allowed to identify the essential elements that could be condensed into a cycle including phases, such as negotiation, protection, assessment, commercialization, among others. According to the literature, these mechanisms must be supported in an institutional policy that guides strategies and organizational processes, mostly those focusing on the product development from the co-creation techniques. The mechanisms presented were formed considering the innovation process used in the ARTICA 2 alliance and those that have been worked in the literature. Also, they were submitted to experts who work with intellectual property in innovation processes for their validation.